LAYANAN PEMBUATAN KARTU KELUARGA DAN KARTU TANDA PENDUDUK DI KECAMATAN KEPAHIANG BERDASARKAN PERDA NOMOR 02 TAHUN 2010 - Stupeu, Oly (Jurnal Governance dan Administrasi Publik, 2017)
This study aims to describe the service of making family cards and citizen cards in Perda No. 02/2010. This research uses descriptive qualitative methods and data collection is done using interview techniques, observation and documentation, data analysis is carried out simultaneously.  The analysis stage consists of four flows, activities that occur simultaneously, namely, (a) data collection, (b) data reduction, (c) data display and, (d) conclusion/ verification. The stages of analysis used above are basically to describe the service for making Family Cards and Identity Cards at the Population and Registry Civil Service Kepahiang Regency based on Kepahiang Regency Regional Regulation Number 02 of 2010 concerning the implementation of Administration  Population. From the research results it can be concluded that the service for making family cards and identity cards owned is good enough, there is no parsing problem